Using animation movie in teaching listening skill - Nuril Ismi Putri; Usman Kasim; Tengku Maya Silvianti (Universitas Syiah Kuala, 2017)
The aim of this research was to find out whether the use of animation affects students’ achievement in listening skill of SMAN 11 Banda Aceh or not. The population of this study was the first grade students and the sample was the students in X IPA 4 where the number of students is 22 chosen by random sampling. The design of this study was a pre-experimental study. To obtain the data, the writer used 20 items of fill in the blank in pre-test and post-test. This research finds that the use of animation movie in the English teaching and learning process was effective to improve the students’ listening skill, especially vocabulary. The result of data collection in this study shows that average post-test score is higher (75.5) than the pre-test score (55.2). The calculation of t-observation (to) 4.20 is higher than t-table (tt) 2.02. It means that Ha is accepted and Ho is rejected. In conclusion, animation movie is an effective media in teaching listening skill. The students become active in discussion during the teaching and learning process.